International Trade and Directed Technical Change in Developing Countries - Minho Kim (KDI Journal of Economic Policy, 2019)
This paper examines the relation between the skill premium and international trade given differences in the relative supply of skills across countries while allowing the South (developing countries) to develop its appropriate technology. Typical assumptions put forward in the literature state that either technology is exogenously given, or technical change is allowed only in the North (developed countries). I present a model of international trade with endogenous growth by allowing the South to direct its technology. The results show that more R&D is directed towards skill-augmenting technology in the North than in the South, in sectors with the same skill-intensity. Technical change induced by lowering trade costs can increase the skill premium in both the North and the South. This result can explain the empirical observation that the skill premium has increased within many developing countries after they experienced trade liberalization. Finally, the model predicts larger gains from trade compared with the model where technical change is either not allowed, or allowed only in the North.
Keywords: F16; F43; O33; O41; 330; Directed Technical Change; Globalization; Economic Growth; Skill Premium